2012
DOI: 10.1167/iovs.11-8720
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of the Anterior Human Corneal Tissue Investigated with Atomic Force Microscopy

Abstract: At microscale level, the mechanical response of the most anterior stroma is complex and nonlinear. The microstructure (fibers' packing, number of cross-links, water content) and the combination of elastic (collagen fibers) and viscous (matrix) components of the tissue influence the type of viscoelastic response. Efforts in modeling the biomechanics of human corneal tissue at micrometric level are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 56 publications
3
65
1
Order By: Relevance
“…1 These mechanical properties stem from the constituent components of the cornea and therefore are governed by factors such as the extracellular matrix and the organization of collagen fibers. 2 The assessment of corneal biomechanical properties has a number of potential clinical applications such as improving the accuracy of IOP measurements, 3,4 the diagnosis of keratoconus (KC), 5 assessing the biomechanical effects of corneal collagen crosslinking (CXL), 6 and assessing the risk of post-LASIK ectasia. 7,8 Recently, the CorVis ST (CST; Oculus, Wetzlar, Germany) was introduced as a clinical tool for the assessment of corneal biomechanical properties in vivo.…”
mentioning
confidence: 99%
“…1 These mechanical properties stem from the constituent components of the cornea and therefore are governed by factors such as the extracellular matrix and the organization of collagen fibers. 2 The assessment of corneal biomechanical properties has a number of potential clinical applications such as improving the accuracy of IOP measurements, 3,4 the diagnosis of keratoconus (KC), 5 assessing the biomechanical effects of corneal collagen crosslinking (CXL), 6 and assessing the risk of post-LASIK ectasia. 7,8 Recently, the CorVis ST (CST; Oculus, Wetzlar, Germany) was introduced as a clinical tool for the assessment of corneal biomechanical properties in vivo.…”
mentioning
confidence: 99%
“…In order to avoid any bias due to changes in the hydration state during the experiment, the corneal tissues were kept in 20% dextran solution overnight before AFM testing. [15][16][17][36][37][38][39] Based on the studies by Hamaoui et al 36 and according to our standardized study protocol, [15][16][17] it was found that 20% dextran solution was effective in avoiding tissue swelling and maintaining corneal hydration during experimentation of riboflavin/UV-A corneal cross-linking. In this study, we indented less than 3 lm anterior stromal depth (which corresponds to the less hydrated part of the cornea; <1% total stromal thickness), and the changes of hydration as well as of indented stroma were therefore considered negligible.…”
Section: 27-29mentioning
confidence: 94%
“…[15][16][17] The mechanical properties of the anterior corneal stroma were measured using an AFM (Multimode 8 Atomic Force Microscope with Nanoscope V controller; Bruker Italy Srl, Milano, Italy) in the force spectroscopy mode according to standardized protocol used in previous studies. 15,17 Measurements were performed at 278C with the specimens immersed in 20% dextran solution, using phosphorus-doped rectangular silicon cantilevers of nominal elastic constant between 20 and 80 N/m (TESPA; Bruker Italia Srl). Dextran was used as imaging medium in order to keep the tissues at the same osmolarity as overnight storage.…”
Section: Afm Data Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations